FACTORS OF STRENGTHENING THE NATIONAL SPIRIT IN IDEOLOGICAL PROCESSES - Shokhakimov A.R. (Bright Mind Publishing, 2025)
The article presents thoughts and opinions on the issues of raising the national spirit and patriotism of military personnel based on the study of the historical roots of our national heritage, wide propaganda of the exemplary life of our great ancestors who showed heroism on the path to freedom of the Motherland.
Keywords: national spirit, courage and bravery, righteous man, ancestral courage, national pride, will, emotion, character, spiritual world, great leader, courage and bravery, virtues, bravery, honor of the nation.